IDENTIFICATION OF MUTATION SITES IN HEPATITIS C VIRUS GENOTYPE 3A IN NON-RESPONDERS TO COMBINATION THERAPY WITH INTERFERON- Î‘LFA AND RIBAVIRIN IN RESIDENTS OF KHYBER PAKHTUNKHWA PROVINCE PAKISTAN - Muhammad, Sardar; Rehman, Mehmud ur; Haq, Najib ul; Khan, Muhammad Mumtaz; Ahmad, Sajjad (Journal of Ayub Medical College Abbottabad, 2016)
Background: This study was carried out to search for mutations in the gene encoding for Non-Structural Protein 5A, specifically in the interferon sensitivity determining region of hepatitis C virus (HCV) genotype 3a, isolated from serum samples of patients not responding to treatment with oral Ribavirin and Interferon alpha injections. Methods: This descriptive case series was conducted on HCV patients reporting in the attached teaching hospitals of Peshawar Medical College selected by consecutive sampling technique from 1st July to 31st December 2012. Amino acid sequencing was performed at the Centre of Applied Molecular Biology Lahore. Patients showing no clinical response after 6 months of combination therapy with Injection Interferon alpha + Ribavirin and still having positive polymerase chain reaction (Declared Non-Responders) were included in this study. Results: Amino acid sequencing was performed on HCV isolates from twenty non-responder and five responder patients. All these sequences were compared with Newzealand1 (NZL1) sequence from the gene bank for mutations; 0-7 mutations were observed in responders as compared to 10-27 mutations in non-responder patients (p value <0.005). Conclusion: We were able to determine that there is a positive correlation between the number of mutations in NS5A ISDR and non-response to combination therapy. Synonymous mutations >10 and non-synonymous mutations >7 in this region suggest poor response to treatment. Keywords: ISDR; NS5A; Non Responders